Phylogenetic relationships and taxonomic issues in Gastridium (Poaceae) inferred from plastid and nuclear DNA sequence analysis. (1st November 2020) - Scoppola, Anna; Cardoni, Simone; Pellegrino, Mariangela; López-Tirado, Javier; Simeone, Marco Cosimo
Abstract: Gastridium P. Beauv. is a Mediterranean-Paleotropical member of the Poaceae family, whose species number and diversity are still imperfectly known. We examined patterns of DNA diversity at two plastid ( trn H- psb A, trn L-F) and one nuclear (ITS) DNA markers in 44 individuals of the four taxa ( Gastridium lainzii, G. phleoides, G. scabrum, G. ventricosum ) recently recognised by different authors, based on morpho-ecological descriptors. Diversity data were explored with multiple statistical and phylogenetic tools, and integrated with available GenBank sequences of Gastridium and closely related genera. Despite the limited variability detected, evidence of within-taxon genetic cohesion and estimates of molecular divergence comparable with those of species in the same subtribal lineage (Agrostidinae) were recovered. The identified plastid genealogies are congruent with a subdivision of the genus into four distinct species, coherently with collected morphological descriptors. Phylogenetic reconstructions with ITS were less corresponding to the four taxa, possibly due to reticulation and polyploidization. The broader plastid and nuclear tree topologies were consistent with previous assessments, highlighting the overall little resolution of species and genera within Agrostidinae, and the close relationships shared by Gastridium and Triplachne . The hypothesis of closely related, but separately evolving, lineages within Gastridium is discussed, suggesting a re-evaluation of its current taxonomy.